COVID-19 and mental distress among health professionals in eight European countries during the third wave: a cross-sectional survey - Dechent, Frieder; Mayer, Gwendolyn; Hummel, Svenja; Moritz, Steffen; Benoy, Charles; Almeida, Rosa; Durán, Raquel Losada; Ribeiro, Oscar; Frisardi, Vincenza; Tarricone, Ilaria; Ferrari, Silvia; Lemogne, Cédric; et al. (Scientific reports, 2024)
Even during the third wave of the COVID-19 pandemic health professionals were facing mental health challenges. The aim of this study was to examine the mental health of doctors, nurses and other professional groups in Europe and to identify differences between the professional groups. We conducted a cross-sectional online survey in 8 European countries. We asked for demographic data, whether the participants were exposed to COVID-19 at work, for main information sources about the pandemic, the Depression Anxiety Stress Scales (DASS-21), and major stressors. A MANCOVA was carried out to find predictors of mental health among health care professionals. The sample (N = 1398) consisted of 237 physicians, 459 nurses, and 351 other healthcare professionals and 351 non-medical professionals with no direct involvement in patient care. The mean mental health of all groups was affected to a mild degree. Major predictors for depression and anxiety were the profession group with higher scores especially in the group of the nurses and working directly with COVID-patients. In the third wave of the COVID-19 pandemic, the psychological burden on health professionals has remained high, with being nurse and working directly with COVID19 patients being particular risk factors for mental distress. We found as a main result that nurses scored significantly higher on depression and anxiety than practitioners.
Gesehen am 09.07.2025